Cytocentric measurement for regenerative medicine - Henn, Alicia D.; Pereira, Taci; Hunsberger, Joshua; Mitra, Kunal; Izadifar, Zohreh; Somara, Sita; Lindström, Lisa; Forest Farb-Horch, Thomas; Boy, Jake; Muschler, George F.; Bauer, Steven R.; Yerden, Randy (Frontiers in Medical Technology, 2023)
Any Regenerative Medicine (RM) business requires reliably predictable cell and tissue products. Regulatory agencies expect control and documentation. However, laboratory tissue production is currently not predictable or well-controlled. Before conditions can be controlled to meet the needs of cells and tissues in culture for RM, we have to know what those needs are and be able to quantify them. Therefore, identification and measurement of critical cell quality attributes at a cellular or pericellular level is essential to generating reproducible cell and tissue products. Here, we identify some of the critical cell and process parameters for cell and tissue products as well as technologies available for sensing them. We also discuss available and needed technologies for monitoring both 2D and 3D cultures to manufacture reliable cell and tissue products for clinical and non-clinical use. As any industry matures, it improves and standardizes the quality of its products. Cytocentric measurement of cell and tissue quality attributes are needed for RM.